Pendampingan Kewirausahaan Peserta Program Pengembangan Kewirausahaan Universitas 17 Agustus 1945 Banyuwangi - Dian Arief Pradana; Herdiana Dyah Susanti; Moh. Fahrurrozi; M. Iswahyudi; Achmad Iqbal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2021)
This service is aimed at increasing the number of entrepreneurs and increasing the business competitiveness of Untag Banyuwangi students and alumni during the covid-19 pandemic. The small number of entrepreneurs, and the pandemic still hasn't ended, makes business people inevitably have to change their business strategies. The Untag Banyuwangi Entrepreneurship Development Program is carried out on the basis of cooperation with the Directorate General of Research Strengthening and Development of the Ministry of Research, Technology and Higher Education. The implementation of mentoring is carried out by providing lighters related to entrepreneurship and business coaching assistance. The results of the service were obtained by 80 alumni students who started their business, after the selection and mentoring process, 5 students were obtained to then be granted patents for the products produced.